Implementation of school-based management - Sugianto, Sugianto; Suroyo, Suroyo; Fatmasari, Rini (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This study examined the influence of teachers' perceptions of management, principals' leadership styles, and teachers' work motivation on the implementation of school-based management in Batang Gansal. This study focuses more on teachers' perceptions and provides a more comprehensive perspective. Multiple regression analysis was employed to test the relationship between the variables. The results demonstrate that effective management influences can enhance principals' performance and expedite the implementation of school-based management. This research contributes to a more nuanced understanding of the factors that influence the successful implementation of school-based management. In other words, the findings of this research can be used to enhance the quality of education in Batang Gansal.